2012
DOI: 10.1155/2012/708423
|View full text |Cite
|
Sign up to set email alerts
|

The Poor Survival among Pulmonary Tuberculosis Patients in Chiapas, Mexico: The Case of Los Altos Region

Abstract: Objective. To analyse survival in patients with pulmonary tuberculosis (PTB) and factors associated with such survival. Design. Study of a cohort of patients aged over 14 years diagnosed with PTB from January 1, 1998 to July 31, 2005. During 2004–2006 a home visit was made to each patient and, during 2008-2009, they were visited again. During these visits a follow-up interview was administered; when the patient had died, a verbal autopsy was conducted with family members. Statistical analysis consisted of surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 5 publications
1
16
0
1
Order By: Relevance
“…Sub-Saharan Africa (SSA) accounts for the lion's share of TB deaths, TB-HIV co-infections, and TB-HIV deaths. One underlying reason is the relatively low coverage and quality of TB prevention, treatment, and care programs in Africa [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa (SSA) accounts for the lion's share of TB deaths, TB-HIV co-infections, and TB-HIV deaths. One underlying reason is the relatively low coverage and quality of TB prevention, treatment, and care programs in Africa [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being the home for around 25% of universally registered cases of TB, sub-Saharan Africa carries a much exceeding share of TB related deaths (40%), TB/HIV co-infections (72%), and TB/HIV deaths (80%); and relatively lowered coverage and worth of TB prevention, care, and treatment programs in Africa are among the many reasons for it (3). Developing countries have a share of 95% of cases and 99% of deaths (4). Ethiopia with 22 high TB burden countries, accounts for nearly 80% of all worldwide TB load and is ranked the 10th globally and the 4th in Africa (1,2,5).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in studies conducted by Van den Broek et al (12) and Albuquerque et al (9), HIV positivity was reported as an important predictive factor of death from tuberculosis. Several factors, such as delays in diagnosis and treatment of HIV-positive patients whose sputum smear is usually negative, and also more advanced immunosuppression, can explain this poor outcome (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although age and treatment duration has been shown in several studies to be associated with death from tuberculosis (7,20,21), we controlled for these factors in our study by individual matching when selecting controls.…”
mentioning
confidence: 99%